Holistic Bullying Prevention in Pesantren: The Role of Peer Support and the Bullyguard Educational Framework - Kumala, Shofa Aulia (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
Bullying in Islamic boarding schools (pesantren) is a pressing issue, considering that Islamic boarding schools should be spaces for character development and religious values. This phenomenon indicates a gap between moral teachings and social practices in the daily lives of students. This study aims to explore the implementation of the BullyGuard approach as a bullying prevention strategy based on education and peer mentoring at the Ma'had Ilmu Al Qur'an (MIQ) Al Hikam Islamic Boarding School in Wonosobo. Using a qualitative approach with a case study design, data were collected through in-depth interviews, participant observation, and documentation, then analyzed thematically using NVivo software. The results show that the BullyGuard approach is able to create a more supportive and child-friendly social environment, with a decrease in cases of verbal and social bullying and increased solidarity among students. The active role of the ustadz, the involvement of administrators, and peer empowerment are key to the success of this model. This research contributes to the development of educational intervention models based on religious values ​​and relevant to the local cultural context of Islamic boarding schools. The conclusion of this study shows that the integration of psychosocial approaches and spiritual values ​​is effective in establishing a safe and inclusive Islamic boarding school ecosystem. Further research is recommended to test this model in various Islamic boarding schools with a mixed methods approach to enrich the findings.